Drugging the ‘undruggable’ KRAS: breakthroughs, challenges, and opportunities in pancreatic cancer - Nawaz Khan; Umar Raza; Syed Aqib Ali Zaidi; Muhadaisi Nuer; Kayisaier Abudurousuli; Yipaerguli Paerhati; Alifeiye Aikebaier; Wenting Zhou (Cancer Biology & Medicine)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with a poor prognosis that is driven primarily by oncogenic KRAS mutations present in > 90% of cases. KRAS mutations, particularly the G12D mutation which dominates in PDAC, fuel tumor initiation, progression, and immune evasion, thereby contributing to therapy resistance. Nevertheless, KRAS has long been considered “undruggable” due to its structure. Recent advances have spurred transformative progress in direct KRAS inhibition. While FDA-approved mutation-specific and pan-KRAS inhibitors show limited efficacy in PDAC, emerging agents (MRTX1133 and RMC-9805) have demonstrated preclinical promise. However, resistance remains a critical hurdle and is driven by pathway reactivation, secondary mutations, and metabolic adaptations. Alternative strategies targeting upstream regulators (SHP2 and SOS1) aim to block KRAS activation and associated resistance mechanisms. Preclinical studies have also highlighted synergistic benefits of combining KRAS inhibitors with MEK, PI3K, or CDK4/6 inhibitors, which are now undergoing clinical evaluation. Immunotherapies, including KRAS-targeted vaccines and adoptive T-cell therapies, have further expanded the therapeutic landscape of enhancing KRAS-targeted therapies in PDAC. The molecular basis of KRAS-driven PDAC, current inhibitors, resistance mechanisms, and innovative strategies are discussed herein to address treatment barriers. Opportunities to improve clinical outcomes are underscored in this challenging malignancy by integrating insights from preclinical and clinical research.